2014
DOI: 10.1038/srep07336
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of epigenetic regulatory genes are common in thymic carcinomas

Abstract: Genetic alterations and etiology of thymic epithelial tumors (TETs) are largely unknown, hampering the development of effective targeted therapies for patients with TETs. Here TETs of advanced-stage patients enrolled in a clinical trial of molecularly-guided targeted therapies were employed for targeted sequencing of 197 cancer-associated genes. Comparative sequence analysis of 78 TET/blood paired samples obtained from 47 thymic carcinoma (TC) and 31 thymoma patients revealed a total of 86 somatic non-synonymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
123
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 56 publications
(95 reference statements)
5
123
5
Order By: Relevance
“…Studies performed in mice with conditional knockout of Dnmt3a revealed a role for DNA methylation in mediating the self-renewal and differentiation of normal hematopoietic stem cells and leukemia stem cells [33]. A functional role of this gene in thymic epithelial tumors emerged from studies that focused on mutation analysis, revealing that DNMT3A is one the most frequently mutated genes in thymic carcinoma [34], and that the mutation p.G728D is associated with B3 thymomas [35]. Similarly, a SNP in the promoter of DNMT3B , namely −579G>T, was associated with TAMG [36], overall suggesting a contribution of de novo DNMTs in thymomas.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in mice with conditional knockout of Dnmt3a revealed a role for DNA methylation in mediating the self-renewal and differentiation of normal hematopoietic stem cells and leukemia stem cells [33]. A functional role of this gene in thymic epithelial tumors emerged from studies that focused on mutation analysis, revealing that DNMT3A is one the most frequently mutated genes in thymic carcinoma [34], and that the mutation p.G728D is associated with B3 thymomas [35]. Similarly, a SNP in the promoter of DNMT3B , namely −579G>T, was associated with TAMG [36], overall suggesting a contribution of de novo DNMTs in thymomas.…”
Section: Discussionmentioning
confidence: 99%
“…Improved genetic 2224 , epigenetic 25, 26 and transcriptomic 24, 27 analyses have augmented our knowledge about the distinct molecular basis of thymomas and thymic carcinomas. The latter show mutations of epigenetic regulatory genes, 22 methylation patterns 26 and expression profiles of anti-apoptotic genes 27 that clearly distinguish them from thymomas.…”
Section: Novelties In the New Who Classification Of Mediastinal Tumorsmentioning
confidence: 99%
“…The latter show mutations of epigenetic regulatory genes, 22 methylation patterns 26 and expression profiles of anti-apoptotic genes 27 that clearly distinguish them from thymomas. On the other hand, the identification of a highly recurrent point mutation in the GTF2I oncogene in all major thymoma subtypes and thymic carcinomas 23 is a seminal finding that underlines the unique tumor biology of thymic epithelial tumors and lends strong support to the WHO-based subtyping of thymic tumors.…”
Section: Novelties In the New Who Classification Of Mediastinal Tumorsmentioning
confidence: 99%
“…Thymic carcinomas have a distinct molecular signature that segregates them from the thymoma subtypes. 6,1623 Such genetic differences, combined with the histology-based classification system, are clinically relevant for both prognosis and treatment of TETs and may contribute to identification of new molecular targets for therapeutic intervention. 3,7,19,20 …”
Section: Introductionmentioning
confidence: 99%